Sistem Informasi Administrasi Multi Cabang pada PT. HC - Lavicius Lavicius; Lily Puspa Dewi; Adi Wibowo (Jurnal Infra, 2017)
Currently, PT. HC records information in Microsoft Excel and physical documents for running business processes. PT. HC has several branches spread across several regions in Indonesia, with the business process of selling products, ordering raw materials and stock storage. Without using information system, accurate and speed in processing and receiving of information at PT. HC and branch are also less good and require a longer time.This application has several main features including sales order, purchase order, warehouse stock recordings, reorder point calculation, invoice payment and generate sales turnover, purchase and stock turnover. This application is made using the programming language HTML, PHP, Javascript and MySQL database. App interface created using Gentellela template with Bootstrap.The final result of the development of this application is able to integrate company information such as sales order records,  purchase orders, invoices, warehouse stock, delivery orders and reports. Users form the center of PT. HC can view sales reports, raw material purchases and stock reports owned by the branch. Users can also receive remainder of some information such as stock that exceeds the minimum stock limit and invoices that exceed the due date through notification in accordance with their respective permissions.